Damage to the human dentate gyrus impairs the perceptual discrimination of complex, novel objects. (29th July 2022) - Mitchnick, K.A.; Ahmad, Z.; Mitchnick, S.D.; Ryan, J.D.; Rosenbaum, R.S.; Freud, E.
Abstract: The hippocampus (HPC), and the dentate gyrus (DG) subregion in particular, is purported to be a pattern separator, orthogonally representing similar information so that distinct memories may be formed. The HPC may also be involved in complex perceptual discrimination. It is unclear if this role is limited to spatial/scene stimuli or extends to the discrimination of objects. Also unclear is whether the DG itself contributes to pattern separation beyond memory. BL, an individual with bilateral DG lesions, was previously shown to have poor discrimination of similar, everyday objects in memory. Here, we demonstrate that BL's deficit extends to complex perceptual discrimination of novel objects. Specifically, BL was presented with closely matched possible and impossible objects, which give rise to fundamentally different 3D perceptual representations despite being visually similar. BL performed significantly worse than controls when asked to select an odd object (e.g., impossible) amongst three identical counterpart objects (e.g., possible) presented at different rotations. His deficit was also evident in an atypical eye fixation pattern during this task. In contrast, BL's performance was indistinguishable from that of controls on other tasks involving the same objects, indicating that he could visually differentiate the object pairs, that he perceived the objects holistically in 3D, and that he has only a mild weakness in categorizing object possibility. Furthermore, his performance on standardized neuropsychological measures indicated intact mental rotation, visual-spatial attention, and working memory (visual and auditory). Collectively, these results provide evidence that the DG is necessary for complex perceptual discrimination of novel objects, indicating that the DG might function as a generic pattern separator of a wide range of stimuli within high-level perception, and that its role is not limited to memory.